Internal carotid artery dissection among younger and older patients with acute ischemic stroke. (3rd April 2018) - Amsalem, Yakov; Porat, L.; Javitt, M. C.; Sprecher, Elliot; Telman, Gregory
ABSTRACT: Purpose/Aim of the study: Carotid artery dissection (CAD) is a known causative factor in the etiology of acute ischemic stroke in young patients. However, the significance of CAD in older patients with acute ischemic stroke is unclear with only a few prior clinical studies. In order to isolate the influence of CAD as an independent factor, we performed multivariate analyses of common covariables in acute ischemic stroke patients in northern Israel. Materials and Methods: Three hundred and forty-seven consecutive patients who suffered from acute ischemic stroke had initial CT angiography (CTA) ordered from the emergency room. We reviewed the CTAs for radiologic signs of CAD, and recorded patients' demographic and clinical data from the hospital's computerized information system. Results: Eighteen of the 347 patients (5.19%) had CTA evidence of CAD, with no statistically significant differences based on age, gender or ethnicity. A statistically significant inverse association between hypertension and a lower rate of CAD was found before and after stepwise logistic regression, while hyperlipidemia showed a trend toward a similar inverse association that was borderline for statistical significance. Conclusions: Our study shows that CAD is an independent and significant causative factor for acute ischemic stroke. Therefore, diagnostic imaging is indicated to rule out CAD not only in young patients, but rather in all patients with acute ischemic stroke. The inverse correlation between common vascular risk factors (i.e. hypertension and hyperlipidemia) and CAD points to CAD as an independent nonatherosclerotic causative factor in the etiology of acute ischemic stroke.